Development and Healing Process of Severe Radiodermatitis in Patients With Head and Neck Cancer Undergoing Radiotherapy: A Scoping Review - Nao Miyamae; Yuko Imakata; Mao Kunimitsu; Makoto Oe (Nursing Research and Practice)
Conclusions: Moist desquamations are more likely to occur in severe radiodermatitis in patients with head and neck cancer. Since they can fuse and spread, preventative measures to mitigate spreading are important. However, there is insufficient information to examine the causes of widespread moist desquamations. For preventing moist desquamations and establishing care methods to heal moist desquamations, it may be necessary to identify the symptoms, site, and shape, including the color tone and depth, and healing process during their occurrence.